Alexander the Great as a portrait of de good ’princeps’ from the writings of Plutarch of Chareonea - Pause, Henrique (Romanitas - Revista de Estudos Grecolatinos, 2024)
Alexandre Magno is one of the most remembered figures in history. Such an emblematic figure in his time, he crossed the borders of the Hellenic world and permeated the imagination of the Roman aristocratic elite, being associated with a military figure, of leadership as well as a divine being and example of ruler. Plutarch of Queroneia, Greek author, but inserted in the Roman society, dedicate two of his countless works to the Macedonian. Based on the works On the Fortune or Virtue of Alexander the Great and the Life of Alexander, we seek in this work to show how, through the virtues, but also the vices of the conqueror of the Persians, Plutarch seeks to educate the one who, according to him, should be the example for all other citizens and inhabitants of the Empire: the Roman princeps.